Step 1) Solve the first equation for #x#:
#x + y = 4#
#x + y - color(red)(y) = 4 - color(red)(y)#
#x + 0 = 4 - y#
#x = 4 - y#
Step 2) Substitute #(4 - y)# for #x# in the second equation and solve for #y#:
#-3x + y = -8# becomes:
#-3(4 - y) + y = -8#
#(-3 xx 4) + (3 xx y) + y = -8#
#-12 + 3y + y = -8#
#-12 + color(red)(12) + 3y + y = -8 + color(red)(12)#
#0 + 3y + y = 4#
#3y + y = 4#
#3y + 1y = 4#
#(3 + 1)y = 4#
#4y = 4#
#(4y)/color(red)(4) = 4/color(red)(4)#
#y = 1#
Step 3) Substitute #1# for #y# in the solution to the first equation at the end of Step 1 and calculate #x#:
#x = 4 - y# becomes:
#x = 4 - 1#
#x = 3#
The Solution Is:
#x = 3# and #y = 1#
Or
#(3, 1)#